(untitled) (Experimental biology, 2023)
A novel coronavirus SARS-CoV-2 has been associated with the COVID-19 atypical pneumonia pandemic, which caused a devastating healthcare and socioeconomic crisis worldwide. Effective diagnosis of the disease is important to prevent the spread of infection. Since the detection of antigens and antibodies against SARS-CoV-2 by enzyme-linked immunosorbent assay is of great importance in the diagnosis of COVID-19, we developed recombinant analogs of the main structural proteins of the SARS-CoV-2 virus. The genes of the main open reading frames, including the surface spike (S) glycoprotein, the small membrane (M) protein, the envelope (E) glycoprotein and nucleocapsid (N) protein, were cloned in expression plasmids pET23c in polyhistidine reading frames. We obtained the strains of Esсherichia coli BL-21(DE3) that produce recombinant S-6His, M-6His, E-6His и N-6His proteins. N-6His protein was produced in sufficient quantities, for the purification of which the conditions of dialysis and its concentration were optimized. We obtained pure preparation of N protein (the target protein concentration is 80%). Further studies should be performed to identify its antigenic activity.